Implementing a Distributed WSN Based on IPv6 for Ambient Monitoring. (4th June 2013) - Larios, D. F.; Mora-Merchan, J. M.; Personal, E.; Barbancho, J.; León, C.
Traditionally, Wireless Sensor Networks (WSNs) are used for monitoring an extensive area. In these networks, a centralized server is usually used to collect and store the sensor information. However, new distributed protocols allow connections directly to the WSN nodes without the need of a centralized server. Moreover, these systems are able to establish communications among heterogeneous networks. The new protocols strategy is focused on considering several WSNs as a unique distributed one. This way, a user of the system is able to analyze a process under study as a whole instead of considering it as a set of different subsystems. This is the case in the evaluation of migratory waterbirds' environment. In this case, it is usual to deploy several WSNs in different breeding areas. They are all interconnected and they measure different environmental parameters. However, this improvement in the data access flexibility may result in a loss of network performance and an increase in network power consumption. Focused on this problem, this paper evaluates different communication protocols: distributed and centralized, in order to determine the best trade-off for environmental monitoring in different migratory areas of waterbirds.